Mindfulness and its measurement - Radoń, Stanisław (Studia Psychologica: Theoria et praxis, 2020)
Mindfulness can be understood as a state, trait or practice. For this reason, there are many uncertainties that result mainly from the lack of precision regarding the mindfulness model. Similar ambiguities exist in the field of research tools to measure the mindfulness. As many researchers prove, these tools measure slightly different psychological constructs. For this reason researchers attempt to distinguish two different aspects of mindfulness, the trait and state, and on this basis develop more accurate research tools. This article is a review of existing measures of mindfulness, taking into account Polish adaptations, showing their specificity.